2020
DOI: 10.1101/2020.05.06.20092700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preexisting Comorbidities Predicting Severe Covid-19 in Older Adults in the UK Biobank Community Cohort

Abstract: Background: Older COVID-19 hospitalized patients frequently have hypertension, diabetes or coronary heart disease (CHD), but whether these are more common than in the population is unclear. During the initial epidemic in England, virus testing for older adults was restricted to symptomatic hospitalized patients. We aimed to estimate associations between pre-existing diagnoses and COVID-19 status, in a large community cohort.Methods: UK Biobank (England) participants assessed 2006 to 2010, followed in hospital … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…Data from the UK Biobank [37], in a prospective case-control study, showed an asthma prevalence of 17.9% in 605 COVID-19 hospitalized patients, most of them adults (the asthma prevalence was of 13.5% in the control population) but the disease was not identified as an independent risk factor for COVID-19 hospitalization/severity, in contrast with hypertension and COPD. In the oldest population (age ≥65 years) included in the UK Biobank [38], the same tendency of asthma prevalence was found between hospitalized COVID-19 patients versus controls (18.2 vs. 13.0%), but again asthma was not identified as an independent risk factor for severity.…”
Section: Methodsmentioning
confidence: 85%
“…Data from the UK Biobank [37], in a prospective case-control study, showed an asthma prevalence of 17.9% in 605 COVID-19 hospitalized patients, most of them adults (the asthma prevalence was of 13.5% in the control population) but the disease was not identified as an independent risk factor for COVID-19 hospitalization/severity, in contrast with hypertension and COPD. In the oldest population (age ≥65 years) included in the UK Biobank [38], the same tendency of asthma prevalence was found between hospitalized COVID-19 patients versus controls (18.2 vs. 13.0%), but again asthma was not identified as an independent risk factor for severity.…”
Section: Methodsmentioning
confidence: 85%
“…To deploy this approach, clinical registries and linked biobanks are a helpful source of information on COVID-19 phenotype variability. The UK Biobank (UKB) has already provided pieces of evidence on COVID-19 [91], and one study matched the inclusion criteria of the present review. By interrogating the UKB, Kuo and coworkers found that ApoE ε4 homozygous individuals are more likely to be COVID-19 test positives compared with ε3 homozygotes, independently from dementia [57].…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In older individuals, comorbidities, such as hypertension, diabetes, obesity, and heart disease, are more likely to promote a cytokine storm resulting in life-threatening respiratory failure and multi-organ damage. 38 42 43 44 Also, respiratory distress is common among most late-stage Alzheimer's disease (AD) patients. 45 Bauer claims that individuals with dementia are more likely to have cardiovascular disease, diabetes, and pneumonia compared to individuals of the same age without dementia.…”
Section: Impact Of Covid-19 On Patients With Cognitive Impairmentmentioning
confidence: 99%